PENGEMBANGAN MEDIA SPINNING WHEEL DALAM BIMBINGAN KELOMPOK UNTUK MENINGKATKAN KOMUNIKASI ASERTIF PADA SISWA SMA NEGERI 1 CIBUAYA - Kamelia, Siti; Hendriana, Heris; Rosita, Tita (FOKUS : Kajian Bimbingan dan Konseling dalam Pendidikan, 2024)
The purpose of this study was to assist students in improving assertive communication, the subjects in this study were 8 class XI students of SMA Negeri 1 Cibuaya who had difficulty in assertive communication. The method used in this research is Research and Development (R&D) while the data collection in this study uses a questionnaire which is calculated by the frequency distribution formula and the N-gain formula. The results of this study indicate that the spinning wheel media that has been developed is declared to be very suitable for use in group guidance to improve assertive communication for students of SMA Negeri 1 Cibuaya, as evidenced by the results of the validation test with the percentage obtained from media experts at 97.3% from material experts at 94, 6% and media users, namely guidance and counseling teachers by 88%. After the spinning wheel media was used in group guidance, the 8 students who were the research subjects experienced an increase in assertive communication in the high category.